Legal Effectiveness of The Pancasila Ideology Development Agency (BPIP) in Giving Recommendations About Regulations that Conflict with Pancasila Values - Hanafi, Anshari Ahmad Syah; Irwansyah, Irwansyah; Aspan, Zulkifli (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to explain the legal effectiveness of BPIP's recommendations on statutory regulations that are contrary to Pancasila values and the main factors that are internal obstacles to BPIP institutions. This type of research uses normative-empirical research. This type of research uses secondary data (from the library) and is supported by primary data based on field research, such as observations, interviews and surveys. Using a normative/juridical approach and a philosophical/ideal values approach. The results of this study are that the implementation of the duties and functions of the BPIP in providing recommendations on regulations that conflict with Pancasila values or the institutionalization of Pancasila values in a product of current legislation is not fully effective due to various influencing factors, including the weak institutionalization of Pancasila values in political institutions. , economic, and socio-cultural, and lack of consistency in making Pancasila the source of all sources of state law in the formation of statutory regulations, BPIP with its duties and functions can provide recommendations on statutory regulations that are contrary to the values of Pancasila but need to be strengthened again the form of the recommendation so that it is final and binding, bearing in mind that the recommendation policy issued by BPIP is only in the form of written input on the contents of regulations or laws that are not in line with Pancasila values.